2022
DOI: 10.3389/fnut.2022.821900
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Probiotics on Respiratory Tract Allergic Disease and Gut Microbiota

Abstract: Allergy is a hypersensitivity reaction triggered by specific cell or antibody-mediated immune mechanisms. Allergies have increased in industrialized countries in recent decades. The rise in allergic respiratory diseases such as allergic rhinitis (AR) and allergic asthma (AA) is a potential threat to public health. Searches were conducted using PubMed, Google Scholar and Medline using the following key terms: allergic rhinitis OR asthma AND probiotics, allergic airway inflammation AND immune disorders, probioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 131 publications
0
21
0
1
Order By: Relevance
“…Additionally, probiotics consolidate the intestinal barrier by increasing mucins, tight junction molecules, and goblet and Paneth cells. Finally, probiotics modulate gut microbiota by ensuring homeostasis and inhibiting the growth of pathogens [ 28 ].…”
Section: The Rationale For Probiotics In Pediatric Asthmamentioning
confidence: 99%
“…Additionally, probiotics consolidate the intestinal barrier by increasing mucins, tight junction molecules, and goblet and Paneth cells. Finally, probiotics modulate gut microbiota by ensuring homeostasis and inhibiting the growth of pathogens [ 28 ].…”
Section: The Rationale For Probiotics In Pediatric Asthmamentioning
confidence: 99%
“…Recently, epidemiological studies have provided evidence for a possible relationship between gut microbiota dysbiosis and the risk of AR ( Chua et al, 2018 ; Su et al, 2021 ; Zhou et al, 2021 ). In addition, numerous studies have reported perturbations in the balance of gut microbiota are correlated with the development and progression of allergic and airway hyperresponsiveness diseases ( Cait et al, 2018 ; Langan et al, 2020 ; Zhang et al, 2021 ; Huang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…This is the case of small chain fatty acids (SCFA) [42] such as butyrate and propionate which are generated in the gut and may diffuse with general circulation to exert their immunoregulatory and anti-inflammatory effects at distant sites in particular controlling Treg expansion [43][44][45][46]. Importantly, the immunomodulating effects of probiotics are not limited to the intestinal mucosa but impact immune responses systemically as it has been demonstrated in allergic disorders [47][48][49]. The immunomodulating and anti-inflammatory effects of probiotics and their ability to normalize gut mucosa permeability may partly explain their beneficial effects in some of the comorbidities of menopause such as osteoporosis and parodontitis.…”
Section: Rationale For the Use Of Probiotics In The Treatment Of The ...mentioning
confidence: 99%